Genotypic variability and correlations among morpho-physiological traits affecting grain yield in barley (Hordeum vulgare L.) - Verma, I; Verma, S R (Journal of Cereal Research, 2011)
Genotypic variability analysis is an important aspect of barley yield improvement. The study was conducted to analyze genotypic variability for yield its component traits and some physiological characters along with analysis of correlations among different traits under normal and late sown conditions. The material of the present investigation consisted of 25 barley genotypes comprising two row and six row types. The experiment was laid out in randomized block design with 25 treatments and replicated thrice in blocks under normal and late-sown conditions in the field. The data revealed significant genotypic variation for all the characters studied viz., grain yield, grain weight, days to heading, biological yield, days to maturity, harvest index, tillers per meter, grains per spike and grain growth rate after 20,27 and 34 days of anthesis, canopy temperature depression(CTD), membrane thermo stability (MTS) and chlorophyll fluorescence. The characters, biological yield, grain weight, days to heading, tillers per meter, harvest index, canopy temperature depression (CTD) were having high mean, wide range, high GCV, PCV, heritability and genetic advance. Correlation coefficients revealed significant positive association of grain yield with harvest index, biological yield and days to maturity in normal sown condition and for biological yield and harvest index in late sown condition. 1000 grain weight had positive and significant correlation with grain growth rate after anthesis. The rate of grain filling is an important trait affecting grain yield.